2022
DOI: 10.1155/2022/9972902
|View full text |Cite
|
Sign up to set email alerts
|

Spectrum-Efficacy Relationships between GC-MS Fingerprints of Essential Oil from Valerianae Jatamansi Rhizoma et Radix and the Efficacy of Inhibiting Microglial Activation

Abstract: The bioactive ingredients of essential oil from Valerianae Jatamansi Rhizoma et Radix (the Rhizome et Radix from Valerianae Jatamansi Jones) (EOVJRR) on the efficacy of inhibiting microglial activation were investigated with the approach of spectrum-efficacy relationship. Fourteen batches of Valerianae Jatamansi Rhizoma et Radix were extracted and analyzed by gas chromatography-mass spectrometry (GC-MS), and their activities in the efficacy of inhibiting microglial activation were assayed by measuring the infl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 39 publications
0
4
0
Order By: Relevance
“…VJJ, with its extensive historical application in TCM, exhibits a wide spectrum of biological activities, including sedative-hypnotic ( Sah et al, 2010 ), antianxiety and antidepressant ( Zhang B. et al, 2021 ; Zhang L. et al, 2021 ), anti-tumour properties ( Tian et al, 2020 ). For CNS, studies have corroborated that VJJ modulates the hypothalamic–pituitary–adrenal axis ( Yan et al, 2010 ; Shi et al, 2014 ), inhibit microglia activation ( Yang et al, 2022 ), and protect the blood–brain barrier ( Zhang B. et al, 2021 ; Zhang L. et al, 2021 ). Contrary to the findings of this study, VJJ has been previously demonstrated to inhibit rotavirus-induced diarrhoea by suppressing the PI3K/AKT signalling pathway ( Zhang et al, 2021 ), and 11-Ethoxyviburtinal, derived from VJJ, exerts anxiolytic effects through this pathway’s inhibition ( Lyu et al, 2023 ).…”
Section: Discussionmentioning
confidence: 99%
“…VJJ, with its extensive historical application in TCM, exhibits a wide spectrum of biological activities, including sedative-hypnotic ( Sah et al, 2010 ), antianxiety and antidepressant ( Zhang B. et al, 2021 ; Zhang L. et al, 2021 ), anti-tumour properties ( Tian et al, 2020 ). For CNS, studies have corroborated that VJJ modulates the hypothalamic–pituitary–adrenal axis ( Yan et al, 2010 ; Shi et al, 2014 ), inhibit microglia activation ( Yang et al, 2022 ), and protect the blood–brain barrier ( Zhang B. et al, 2021 ; Zhang L. et al, 2021 ). Contrary to the findings of this study, VJJ has been previously demonstrated to inhibit rotavirus-induced diarrhoea by suppressing the PI3K/AKT signalling pathway ( Zhang et al, 2021 ), and 11-Ethoxyviburtinal, derived from VJJ, exerts anxiolytic effects through this pathway’s inhibition ( Lyu et al, 2023 ).…”
Section: Discussionmentioning
confidence: 99%
“…This approach can benefit from both the synergistic and additive effects of compounds present within a mixture, thus exerting a better activity. Plants used as a source of EOs for the investigation of their influence on microglia were species belonging to the families of Apiaceae [22], Asteraceae [23][24][25], Cupressaceae [26], Ericaceae [27], Lamiaceae [28], Valerianaceae [29], and others [30]. Some plant species are used traditionally, especially in Chinese medicine, for treating CNS disorders [31], while some have previously been proven to possess anti-inflammatory activity [30,32,33].…”
Section: The Potential Of Essential Oils To Modulate Microglia and Mi...mentioning
confidence: 99%
“…The EO and compound-rich fractions isolated from V. jatamansi rhizoma et radix were evaluated in vitro for their ability to inhibit primary mouse microglial cell activation by LPS (Table 1). It was determined that different fractions exert a more or less pronounced effect on supressing IL-1β and IL-6 production [29]. There has been an established relationship between the chemical composition of the EO from V. jatamansi rhizoma et radix in inhibiting microglial activation.…”
Section: Eos Associated With Plants Used In Chinese Traditional Medicinementioning
confidence: 99%
See 1 more Smart Citation